Dissociating retrieval interference and reanalysis in the P600 during sentence comprehension - Tanner, Darren; Grey, Sarah; Hell, Janet G. van (Psychophysiology, 2017)
We investigated the relative independence of two key processes in language comprehension, as reflected in the P600 ERP component. Numerous studies have linked the P600 to sentence- or message-level reanalysis; however, much research has shown that skilled, cue-based memory retrieval operations are also important to successful language processing. Our goal was to identify whether these cue-based retrieval operations are part of the reanalysis processes indexed by the P600. To this end, participants read sentences that were either grammatical or ungrammatical via subject-verb agreement violations, and in which there was either no possibility for retrieval interference or there was an attractor noun interfering with the computation of subject-verb agreement (e.g., “The slogan on the political poster(s) was/were …”). A stimulus onset asynchrony manipulation (fast, medium, or slow presentation rate) was designed to modulate participants' ability to engage in reanalysis processes. Results showed a reliable attraction interference effect, indexed by reduced behavioral sensitivity to ungrammaticalities and P600 amplitudes when there was an opportunity for retrieval interference, as well as an effect of presentation rate, with reduced behavioral sensitivity and smaller P600 effects at faster presentation rates. Importantly, there was no interaction between the two, suggesting that retrieval interference and sentence-level reanalysis processes indexed by the P600 can be neurocognitively distinct processes.